A Study about New Variations for the Spin-Based Multiprocessor Priority Ceiling Protocol - Carminati, Andreu; Oliveira, Rômulo Silva de Silva de (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2012)
The objective of this paper is to propose spin-based (busy waiting in case of blocking) variations for the Multiprocessor Priority Ceiling Protocol. The variations are compared with existing protocols for the same system model, which is partitioned scheduling and fixed priority, as the Flexible Multiprocessor Locking Protocol. The proposed variations simplify some characteristics, such implementation or reducing the number of processors needed to schedule synthetic sets of tasks, as used in this work.